Shifts in Ectomycorrhizal Fungal Communities and Exploration Types Relate to the Environment and Fine-Root Traits Across Interior Douglas-Fir Forests of Western Canada - Defrenne, Camille E.; Philpott, Timothy J.; Guichon, Shannon H. A.; Roach, W. Jean; Pickles, Brian J.; Simard, Suzanne W. (Frontiers in Plant Science, 2019)
Large-scale studies that examine the responses of ectomycorrhizal fungi across biogeographic gradients are necessary to assess their role in mediating current and predicted future alterations in forest ecosystem processes. We assessed the extent of environmental filtering on interior Douglas-fir (Pseudotsuga menziesii var. glauca (Beissn.) Franco) ectomycorrhizal fungal communities across regional gradients in precipitation, temperature, and soil fertility in interior Douglas-fir dominated forests of western Canada. We also examined relationships between fine-root traits and mycorrhizal fungal exploration types by combining root and fungal trait measurements with next-generation sequencing. Temperature, precipitation, and soil C:N ratio affected fungal community dissimilarities and exploration type abundance but had no effect on fungal richness and α-diversity. Fungi with rhizomorphs (e.g., Piloderma sp.) and/or proteolytic abilities (e.g., Cortinarius sp.) dominated communities in warmer and less fertile environments. Ascomycetes (e.g., Cenococcum geophilum) and/or shorter distance explorers, which are potentially cost the plant less C, were favored in colder/drier climates where soils were richer in total nitrogen. Environmental filtering of ectomycorrhizal fungal communities is potentially related to co-evolutionary history between Douglas-fir populations and fungal symbionts, suggesting success of interior Douglas-fir as climate changes may be dependent on maintaining strong associations with local communities of mycorrhizal fungi. No evidence for a link between root and fungal resource foraging strategies was found at the regional scale. This lack of evidence further supports the need for a separate mycorrhizal symbiosis framework, independent from root trait frameworks, to aid in understanding below-ground plant uptake strategies across environments.